Psychiatric Functioning and Quality of Life in Young Patients With Cardiac Rhythm Devices - Webster, Gregory (American Academy of Pediatrics, 2014)
BACKGROUND: Less is known about depression, anxiety and quality of life (QoL) in children and adolescents with pacemakers (PMs) and implantable cardioverter-defibrillators (ICDs) than is known in adults with these devices. METHODS: A standardized psychiatric interview diagnosed anxiety/depressive disorders in a cross-sectional study. Self-report measures of anxiety, depression and post-traumatic stress disorder were obtained. Medical disease severity, family functioning and QoL data were collected. A total of 166 patients were enrolled (52 ICD, 114 PM; median age 15 years). RESULTS: Prevalence of current and lifetime psychiatric disorders was higher in patients with ICDs than PMs (Current: 27% vs. 11%, P = .02; Lifetime: 52% ICD vs. 34% PM, P = .01). Patients with ICDs had more anxiety than a healthy population (25% vs. 7%, P < .01). Patients with ICDs and PMs had similar levels of depression as a healthy population (ICD 10%, PM 4%, reference 4%, P = .29). In multivariate analysis including a medical disease score, demographics, exposure to beta-blockers, activity limitations, hospitalizations, shocks and procedures, the type of device (PM versus ICD) did not predict psychiatric diagnoses when age at implantation and the severity of medical disease were controlled for. Patients with ICDs and PMs had lower physical QoL scores (ICD 45, PM 47.5, Norm 53, P ≤ .03), but similar psychosocial functioning scores (ICD 49, PM 51, Norm 51, P ≥ .16) versus a normal reference population. CONCLUSIONS: Anxiety is highly prevalent in young patients with ICDs, but the higher rates can be attributed to medical disease severity and age at implantation instead of type of device.